The nexus between entrepreneurial and market orientation on digital marketing capabilities and marketing performance of SMEs in emerging markets - Hosianna Ayu Hidayati; Endang Siti Astuti; Andriani Kusumawati; Mohammad Iqbal (Cogent Business & Management)
Entrepreneurial marketing has been conceptualized to address challenges encountered by small and medium-sized enterprises (SMEs), particularly those operating with limited resources and under dynamic environmental conditions. This study investigates the extent to which entrepreneurial orientation and market orientation predict digital marketing capabilities and enhance marketing performance in the context of SMEs in emerging markets. This study employs a quantitative approach through a survey-based design with a self-administered (structured) questionnaire. The sample size of 398 SMEs was determined using Slovin’s formula, and data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), a robust technique commonly adopted in marketing research. These findings reveal that entrepreneurial orientation has a significant direct effect on digital marketing capabilities and marketing performance. Similarly, market orientation exerts a positive and significant impact on both digital marketing capabilities and marketing performance. Furthermore, digital marketing capability significantly influences marketing performance and mediates the relationship between entrepreneurial orientation and marketing performance, as well as between market orientation and marketing performance. These findings underscore the strategic role of entrepreneurial and market orientations as foundational drivers of digital marketing capability and overall marketing performance in resource-constrained and volatile business environments.